Organizational Citizenship Behavior (OCB) Karyawan pada Perusahaan - Dian Anggraini Kusumajati (Bina Nusantara University, 2014)
Human resources are the most important asset in a company to get success of an organization/company. Many organizations face challenges such as how organizations respond to change from external and adapt to internal environment of organization. In this case OCB can increase organizational performance, because this behavior is the